Characterization of the laminated carbon fiber with perlon layers for prosthetic socket applications: Numerical and experimental analysis - Hussein Kadhim Sharaf; Noor Fakher Khdr; Jumaa S. Chiad (Next Materials)
The aim of this study was to examine the characterization of composite materials with an orthotropic component. A lamination was done using two layers of carbon fiber and two layers of Perlon to make prosthetic applications. The results of the tensile and fatigue tests were carefully calculated with the use of a test rig, which made it possible to accurately describe the material. Numerical simulations were used to model and mesh the geometry, and the Static Structural tool was used to do the modeling and meshing. The three steps of applying force were 100 N, 200 N, and 400 N. The ANSYS software was used to examine the results of the simulation, and it was found that the highest normal stress was 19.9 MPa. After looking at how much the object changed shape along three axes (X, Y, and Z), it was found that the X-axis changed shape the most, by 0.009 mm. Normal theory was also used to look at how fatigue works to figure out the failure criterion. The current materials underwent the standard fatigue test, demonstrating a fatigue life of 4300,000 cycles.